From Spandau to Guantanamo: prisons as Propaganda Instruments for Extremists and Terrorists - Thompson, Nathan (Perspectives on terrorism, 2021)
Prisons have featured repeatedly in narratives of terrorist and other violent extremist groups. Such groups have exploited the imprisonment of their members as a propaganda tool aimed at eliciting support and attracting new members through discourses of struggle and oppression. This article examines three such cases, to isolate key elements that support the use of prisons as a symbol of the ideological struggle of violent militants. It encompasses cases of right-wing extremism as well as nationalist and religious terrorism. With an emphasis on illustrating how terrorist groups utilize prisons to achieve various aims, this article seeks to provide a preliminary understanding of the symbolic and iconic use of prisons across a variety of ideologies. Greater understanding of the factors that promote the choice of prisons as symbols of ideological legitimization could serve to support approaches to minimise the representation of prisons in legitimizing ideologically motivated violence.